2022
DOI: 10.1186/s12944-022-01679-x
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial triglyceride levels rather than fat distribution may reflect early signs of disturbed fat metabolism in Iraqi immigrants

Abstract: Purpose Previous studies have shown that at a similar body mass index, Middle Eastern immigrants are more insulin resistant and at higher risk for type 2 diabetes (T2D) than native Europeans. Insulin resistance is strongly associated with disturbed fat metabolism and cardiovascular disease (CVD). However, fat metabolism is poorly investigated comparing Middle Eastern and European ethnicities. Methods This observational study included 26 Iraqi and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Apo C3 reflects the risk of postprandial TG disorders ( 46 ). Instead of fat distribution, postprandial TG levels may reflect early fat metabolic disturbances ( 47 ). Chinese people with fasting TG levels in the range of 1.0 to 1.7 mmol/L may benefit most from OFTT to identify postprandial dyslipidemia ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apo C3 reflects the risk of postprandial TG disorders ( 46 ). Instead of fat distribution, postprandial TG levels may reflect early fat metabolic disturbances ( 47 ). Chinese people with fasting TG levels in the range of 1.0 to 1.7 mmol/L may benefit most from OFTT to identify postprandial dyslipidemia ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…We could not find any cardiovascular risk factors explaining the variation in myocardial perfusion across males of Middle Eastern and Caucasian origin. From the same MEDIM cohort as the current study is based on two studies on differences in fat metabolism have recently demonstrated that (1) healthy Iraqi male immigrants displayed a higher triglyceride peak and a delayed postprandial triglyceride clearance compared with Swedes after an oral fat tolerance test 33 and (2) Iraqi-born men presented a more favorable abdominal fatty-acid composition compared to Swedish-born men using MRI of the abdomen 34 .…”
Section: Discussionmentioning
confidence: 99%